Compact 60 GHz low‐temperature cofired ceramic filter with quasi‐elliptic bandpass response. Issue 6 (1st April 2016) - Wang, Desong; Chin, Kuo‐Sheng; Che, Wenquan; Wu, Yafen; Chang, Chih‐Chun
Abstract : This study presents a 60 GHz quasi‐elliptic bandpass filter with a compact and planar structure. The proposed filter was constructed by stacking substrate integrated waveguide (SIW) cavities on the central transverse plane of a shielding SIW cavity. Jerusalem cross (JC) apertures and circular apertures were etched on the metal layers of the stacked SIW cavities to enable dual‐mode operation and energy coupling. In the dual‐mode cavities, the TM110 cavity mode and JC aperture mode can be excited simultaneously. Cross‐mutual couplings exist among the resonant modes, resulting in two finite transmission zeros with each at either side of the passband. Multilayer low‐temperature cofired ceramic technology was adopted to manufacture the experimental filter. The measured centre frequency was 60 GHz at a fractional bandwidth of 4.5% with two finite transmission zeros located at 53.7 and 65 GHz, thereby achieving high‐frequency selectivity.